Details of the Garbhagriha's entrance of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
Details of the garbhagriha (sanctum sanctorum) entrance of the Bhandasar Temple. The beam, pilasters and brackets are covered with meenakari (enamel) gold work. The walls flanking the entrance opening have the same floral paintings found on the walls and ceiling of the temple.